DEKONSTRUKSI KONSEP GOOD UNIVERSITY GOVERNANCE DALAM PELAKSANAAN ANGGARAN PERGURUAN TINGGI NEGERI BADAN HUKUM - L Lussiana; Titik Mildawati; F Fidiana (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
This study aims to deconstruct the concept of Good University Governance in the implementation of the budget of Legal Entity State Universities (PTN-BH). Therefore an approach is needed that can expose the concept of Good University Governance in a budget implementation. This research is conceptual research. Researchers are motivated to formulate the concept because they see that the budget in an institution has an important role in determining the results of organizational performance. Legal Entity State Universities are required to compile organizational performance reports in accordance with Menristek Dikti Regulation Number 40 of 2016. Indicators of organizational performance assessment for PTN-BH based on Menristek Dikti Regulation Number 40 of 2016 are must meet Good University Governance which consists of transparency, accountability, responsibility, effective and efficient. The success of the PTN-BH budget implementation is in fact measured by the fulfillment of Good University Governance. Therefore it is necessary to first understand the concept of Good University Governance in implementing the PTN-BH budget. This study uses contextual concepts by understanding existing theories and relating them to existing reality / daily life.